2002
DOI: 10.1159/000067812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mirtazapine on Sleep Polygraphic Variables in Major Depression

Abstract: Mirtazapine, a noradrenergic and specific serotonergic antidepressant(NaSSA), was administered on a flexible schedule in a sample of 17 drug-free patients meeting DSM-IV criteria for a major depressive episode. Sleep polygraphic recordings were performed before and during acute and chronic treatment. Severity of depression and subjective assessment of changes within different aspects of sleep were also evaluated. During the acute administration (first 2 days), mirtazapine significantly increased total sleep ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 17 publications
4
34
2
1
Order By: Relevance
“…This methodological issue may contribute to differences between nights À1 and 2. Two studies reported an increase of REM latency: one in healthy subjects (Ruigt et al, 1990) and the other in depressed patients (Schittecatte et al, 2002a). This finding could not be replicated in all other reports (Winokur et al, 2000(Winokur et al, , 2003Aslan et al, 2002), including the present study.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…This methodological issue may contribute to differences between nights À1 and 2. Two studies reported an increase of REM latency: one in healthy subjects (Ruigt et al, 1990) and the other in depressed patients (Schittecatte et al, 2002a). This finding could not be replicated in all other reports (Winokur et al, 2000(Winokur et al, , 2003Aslan et al, 2002), including the present study.…”
Section: Discussioncontrasting
confidence: 92%
“…When compared to baseline, sleep latency decreased and total sleep time and sleep efficiency increased during week 1 with similar results in week 2 (Winokur et al, 2000). In a larger sample, Schittecatte et al (2002a) found more distinct sleep-improving effects of mirtazapine. Already after 2 days administration of 15 mg, total sleep time, sleep efficiency index, and time spent in stage 2, REM, and SWS increased, whereas sleep latency and stage awake decreased.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations